2021
DOI: 10.5194/acp-2021-532
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is the ocean surface a source of nitrous acid (HONO) in the marine boundary layer?

Abstract: Abstract. Nitrous acid, HONO, is a key net photolytic precursor to OH radicals in the atmospheric boundary later. As OH is the dominant atmospheric oxidant, driving the removal of many primary pollutants and the formation of secondary species, a quantitative understanding of HONO sources is important to predict atmospheric oxidising capacity. While a number of HONO formation mechanisms have been identified, recent work has ascribed significant importance to the dark, ocean-surface mediated conversion of NO2 to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…4a), with maxima of ∼ 3 pptv around solar noon and minima near or below ∼ 1 pptv during the early morning hours before sunrise. The observed diurnal trends of HONO were in good agreement with those observed from the Cape Verde Atmospheric Observatory located in the tropical Atlantic boundary layer (Crilley et al, 2021;Kasibhatla et al, 2018;Reed et al, 2017;Ye et al, 2017a). At night, HONO concentrations reached steady-state concentrations of ∼ 1 and 0.7 pptv for the spring and summer season, respectively; these nocturnal HONO concentration steady states were consistent with previous reports in the clean marine boundary layer (Crilley et al, 2021;Kasibhatla et al, 2018;Reed et al, 2017;Ye et al, 2017a).…”
Section: Diurnal Variationssupporting
confidence: 90%
See 2 more Smart Citations
“…4a), with maxima of ∼ 3 pptv around solar noon and minima near or below ∼ 1 pptv during the early morning hours before sunrise. The observed diurnal trends of HONO were in good agreement with those observed from the Cape Verde Atmospheric Observatory located in the tropical Atlantic boundary layer (Crilley et al, 2021;Kasibhatla et al, 2018;Reed et al, 2017;Ye et al, 2017a). At night, HONO concentrations reached steady-state concentrations of ∼ 1 and 0.7 pptv for the spring and summer season, respectively; these nocturnal HONO concentration steady states were consistent with previous reports in the clean marine boundary layer (Crilley et al, 2021;Kasibhatla et al, 2018;Reed et al, 2017;Ye et al, 2017a).…”
Section: Diurnal Variationssupporting
confidence: 90%
“…4). Nighttime steady states in HONO concentrations were previously reported in a clean (Crilley et al, 2021;Kasibhatla et al, 2018;Reed et al, 2017;Ye et al, 2017a) and polluted marine environment (Wojtal et al, 2011). Several recent research works showed nighttime HONO accumulations in polluted marine environments (Wen et al, 2019;Wojtal et al, 2011;Yang et al, 2021;Zha et al, 2014).…”
Section: Diurnal Variationsmentioning
confidence: 77%
See 1 more Smart Citation
“…Nitrous acid (HONO) has a pivotal role in tropospheric chemistry as an important source of the hydroxyl radical (OH) (1)(2)(3)(4)(5)(6)(7). It has also been proposed as a substantial source of NO x (NO and NO 2 ) to the remote marine environment (8)(9)(10). NO x regulates the abundance of atmospheric oxidants and is essential for the formation of secondary atmospheric aerosols, and OH controls the self-cleansing capacity of the atmosphere via degradation of pollutants and greenhouse gases such as methane (1).…”
Section: Introductionmentioning
confidence: 99%
“…It is now generally accepted that HONO can be directly emitted into the atmosphere from traffic, soil emissions, etc. (Kirchstetter et al., 1996; Su et al., 2011; Xu et al., 2015), while it can also be formed through gas‐phase or heterogeneous reactions, including the gas‐phase reaction of NO with • OH (Kleffmann, 2007; Lee et al., 2016), heterogeneous reactions and photosensitized conversion of NO 2 on various surfaces (Crilley et al., 2021; Finlayson‐Pitts et al., 2003; George et al., 2005; Stemmler et al., 2006), photolysis of nitric acid and nitrate anions (NO 3 − ) (Scharko et al., 2014; Wang, Dalton, et al., 2020; Zhou et al., 2003, 2011), neonicotinoid nitenpyram ozonolysis (Wang, Ezell, et al., 2020) and nitroaromatic compounds photolysis (Bejan et al., 2006; Li et al., 2020; Meusel et al., 2017; You et al., 2022). Besides, local micrometeorological processes, such as the formation of an atmospheric stable decoupled layer at the ground level, can significantly influence the HONO concentrations in the air (Wang, Li, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%